2010
DOI: 10.1002/hyp.7974
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometeorology of tropical montane cloud forests: emerging patterns

Abstract: Abstract:Tropical montane cloud forests (TMCF) typically experience conditions of frequent to persistent fog. On the basis of the altitudinal limits between which TMCF generally occur (800-3500 m.a.s.l. depending on mountain size and distance to coast) their current areal extent is estimated at ¾215 000 km 2 or 6Ð6% of all montane tropical forests. Alternatively, on the basis of remotely sensed frequencies of cloud occurrence, fog-affected forest may occupy as much as 2Ð21 Mkm 2 . Four hydrologically distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
283
4
13

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(334 citation statements)
references
References 192 publications
(290 reference statements)
9
283
4
13
Order By: Relevance
“…We found that additional water inputs due to CWI were comparatively low (< 2% of 3180 mm yr -1 and 8% of dryseason rainfall of 640 mm), which was largely attributed to the relatively infrequent occurrence of dense fog and, especially, low wind speeds (Holwerda et al 2010, Alvarado-Barrientos et al 2014. Our cloud forest site falls at the low end of the global range for CWI, while the estimated ET (1325 mm yr -1 ) (Muñoz-Villers et al 2012) is at the higher end of the global range (Bruijnzeel et al 2011). These findings contrast with many other studies conducted in (foggier or windier) cloud forest sites that showed a much greater annual water recharge (i.e., CWI inputs minus ET losses) (Holwerda 2005, Holwerda et al 2006, McJannet et al 2007).…”
Section: Introductioncontrasting
confidence: 88%
See 2 more Smart Citations
“…We found that additional water inputs due to CWI were comparatively low (< 2% of 3180 mm yr -1 and 8% of dryseason rainfall of 640 mm), which was largely attributed to the relatively infrequent occurrence of dense fog and, especially, low wind speeds (Holwerda et al 2010, Alvarado-Barrientos et al 2014. Our cloud forest site falls at the low end of the global range for CWI, while the estimated ET (1325 mm yr -1 ) (Muñoz-Villers et al 2012) is at the higher end of the global range (Bruijnzeel et al 2011). These findings contrast with many other studies conducted in (foggier or windier) cloud forest sites that showed a much greater annual water recharge (i.e., CWI inputs minus ET losses) (Holwerda 2005, Holwerda et al 2006, McJannet et al 2007).…”
Section: Introductioncontrasting
confidence: 88%
“…For example, some PHS schemes (Quintero et al 2009: Ecuador;Muñoz-Piña et al 2008: Mexico) attribute greater hydrologic value and, in turn, payment compensation to cloud forests because of their (presumably) higher water yield over other forests due to a combination of high rainfall, additional fog deposition inputs, and low evapotranspiration losses (cf. Bruijnzeel et al 2011). Other programs have attempted to identify areas of greater hydrologic priority based on recharge zones (Peñuela-Arévalo and Carrillo-Rivera 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CF world surface area consists of ca. 215,000 km 2 [5], constituting an average 6.6% of the world's tropical forests [6]. CF forests have scarce continuous vegetation cover and their restricted distribution makes them sensitive to isolation owing to the deforestation processes in recent years [7].…”
Section: Introductionmentioning
confidence: 99%
“…CF forests have scarce continuous vegetation cover and their restricted distribution makes them sensitive to isolation owing to the deforestation processes in recent years [7]. Since the 1990s, CF ecosystems have been classified amongst the most threatened terrestrial ecosystems [6], showing a deforestation rate during 1981-1990 much higher than that of lowland woods (1.1% vs. 0.8% yearly, respectively; [8]) causing a decrease in 19.3% of its original global cover [7], whilst a recent small scale study has shown a deforestation rate for 1986-2006 of 0.72% [9].…”
Section: Introductionmentioning
confidence: 99%